ROLE OF KNOWLEDGE SHARING IN INTELLECTUAL CAPITAL AND COMPANY PERFORMANCE: CHALLENGES IN INDUSTRY 4.0 ERA - Ira Hapsari; Annisa Ilma Hartikasari (Universitas Pandanaran, 2019)
This research aims to examine the effect of intellectual capital toward financial and operationalperformance with knowledge sharing as mediating variable in industry 4.0 era. Populations inthis research were commercial banks listed in Indonesia Stock Exchange during 2016-2018periods. Samples were taken by purposive sampling technique and obtained 60 data from 20commercial banks with certain criteria. This research used both secondary data from annualfinancial reports and questionnaires were also developed to gather information fromrespondents. Data were analyzed using path analysis with SmartPLS 3.00. The result showedthat intellectual capital has positive effect toward both financial performance and operationalperformance. Tacit knowledge sharing and explicit knowledge sharing fully mediating theeffect of Intellectual capital toward financial performance. While, tacit knowledge sharing andexplicit knowledge sharing partially mediating the effect of intellectual capital towardoperational performance.Keywords: Industry 4.0, intellectual capital, knowledge sharing, performance